2019
DOI: 10.17582/journal.pjz/2020.52.1.sc11
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Abundance of Vertebrate Pests of Cultivated Maize and their Eco-Friendly Management in District Bagh, Azad Jammu and Kashmir, Pakistan

Abstract: Authors' Contributions AHF presented the main idea of research. FA arranged the funding and supervised the research. MH did statistical analysis. LZF conducted lab work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…The present study reports the use of 19 species as fruits and vegetables, also confirm the findings (Faiz et al 2014) reported in Lesser Himalayas in Tolipir landscape. The use of the species (J. mesnyi, C. alba, A. incisum, C. rosthornii) as ornamental and spiritual purposes also confirm the findings (Faiz et al 2014) reported in Lesser Himalayas in Tolipir landscape. In all, 47 species are used for medicinal purposes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present study reports the use of 19 species as fruits and vegetables, also confirm the findings (Faiz et al 2014) reported in Lesser Himalayas in Tolipir landscape. The use of the species (J. mesnyi, C. alba, A. incisum, C. rosthornii) as ornamental and spiritual purposes also confirm the findings (Faiz et al 2014) reported in Lesser Himalayas in Tolipir landscape. In all, 47 species are used for medicinal purposes.…”
Section: Resultssupporting
confidence: 91%
“…These actions will also have a positive impact on lowland ecosystems that depend on the sustainability of these mountain ecosystems. A lot of studies on Lesser Himalayas have been done by Faiz et al 2014, Faiz and Fakhr 2015a, 2015b, 2015c but the results of this study provide quantitative information on the natural vegetation of the Pir Punjal range. This contribution also assesses the importance and roles this plant diversity provides the ecosystem, with the overall aim being the identification of those plant species and communities at greatest risk of overuse and loss.…”
Section: Introductionmentioning
confidence: 93%
“…The highest seasonal Shannon index (4.3) of bird species was recorded in summer followed by autumn (3.99), winter (3.64) and spring (3.58) (Figure 3), while its overall value was recorded to (3.9). Faiz et al [18] surveyed Toli pir national park, district Poonch, Azad Kashmir, Pakistan and calculated overall diversity index (2.22), while Raza et al [19], reported the avian diversity of Lahore zoo safari, overall diversity index was recorded to be (1.93). Sidra & Ali [20] during the survey of new campus Punjab university estimated it to be (2.548).…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%
“…Post-harvest loss can be explained as degradation in volume, value and nutrition (Chitranshi et al, 2020). Considerable amount of food is gone in post-harvest (Faiz et al, 2020). Moreover, the fungi and nematodes are also posing a serious threat to our crops (Parveen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%